Promotion of Acetylene Reduction by Rhizobium-Soybean Cell Associations in Vitro - Phillips, Donald A. (1974)
Nitrogenase activity, determined by the acetylene reduction assay, in soybean cell suspensions infected with Rhizobium, was stimulated significantly by the addition of succinic acid or glutamine. Acetylene-dependent ethylene values as high as 4.6 μmoles of ethylene/gram dry weight·hour were observed.